Political Performances of Control During COVID-19: Controlling and Contesting Democracy in Germany - Volk, Sabine (Frontiers in Political Science, 2021)
Drawing from interpretive, namely discursive-performative approaches to both institutional and grassroots (populist) politics, this article explores political performances and counter-performances of control in Germany during the so-called first wave of the COVID-19 pandemic. Methodologically, the article constructs a comparative analytical framework including three cases from both within and outside of the federal institutional structure of Germany: at the institutional level, the cases comprise Angela Merkel, long-term federal Chancellor of Germany, and Michael Kretschmer, the regional Governor of the state of Saxony; at the grassroots level, the selected case is the populist protest movement “Patriotic Europeans Against the Islamization of the Occident” (Patriotische Europäer gegen die Islamisierung des Abendlandes, PEGIDA). Based on original empirical data generated using the toolkit of qualitative-interpretive methodology, notably online ethnography, the comparative analysis focuses on a few key counter-performances of control, among them a TV address (Merkel), a visit to an “anti-lockdown” demonstration (Kretschmer), and virtual protest events (PEGIDA). Emphasizing the performed, dynamic, and contested character of political control in Germany in spring 2020, the empirical analysis yields the following results: first, it sheds light on the different political styles of performing and contesting institutional control, including the habitus, modes, and (emotional) tones of the communication of the performers, and the scripts, stages, intended audiences as (imagined) constituencies, and modalities of transmission of their performances. Second, the discourse-theoretical perspective of the analysis reveals that political performances of control were closely linked to articulations of democracy as an empty signifier, and to claims for safeguarding democratic principles as such. Third, the article demonstrates the value of interpretive approaches to politics to generate more nuanced understandings of the relationships between the pandemic, democracy, and populism in a situation of an ultimate lack of control.